Strategic management - Rothaermel, Frank T. (New York, NY : McGraw-Hill Education, 2021)
'Strategic Management brings conceptual frameworks to life via examples that cover products and services from companies with which students are familiar, such as Facebook, Google, Tesla, Starbucks, Apple, McDonald's, Disney, Airbnb, and Uber. Liberal use of such examples aids in making strategy relevant to students' lives and helps them internalize strategy concepts and frameworks'--
Includes references and index.
Buku bacaan asas Fakulti Ekonomi Pengurusan.
Keywords: Strategic planning; Management